2019
DOI: 10.1007/s11482-018-9690-4
|View full text |Cite
|
Sign up to set email alerts
|

Character Strengths – Stability, Change, and Relationships with Well-Being Changes

Abstract: Character strengths are positively valued personality traits that are assumed to be stable across time and situations, but also malleable due to cultivation or deliberate intervention. Also, studies showed that character strengths are robustly related to well-being. Consequently, character strengths have often been used in interventions aimed at increasing well-being. However, the stability of character strengths and the longitudinal relationships with well-being are widely unexplored: First, previous reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 44 publications
(55 reference statements)
3
41
1
5
Order By: Relevance
“…Character strengths are trait-like personality characteristics; they exhibit a reasonable amount of stability over time and situations, but they are nevertheless influenced by life circumstances and might therefore change over the life course or as the result of training (cf. Gander et al 2019).…”
Section: Character Strengthsmentioning
confidence: 99%
“…Character strengths are trait-like personality characteristics; they exhibit a reasonable amount of stability over time and situations, but they are nevertheless influenced by life circumstances and might therefore change over the life course or as the result of training (cf. Gander et al 2019).…”
Section: Character Strengthsmentioning
confidence: 99%
“…First, most relationships were rather small by conventional standards. This can partially be explained by the use of a short form for the assessment of character strengths (i.e., the Character Strengths Rating Form; CSRF); studies that compared findings of this instrument with the standard instrument (i.e., the VIA-IS) confirmed that, when using the CSRF, relationships are generally underestimated but show a highly similar pattern (Ruch et al, 2014;Gander et al, 2020). Nonetheless, most participants scored rather high in most strengths, and more fine-grained measures of character strengths might yield more appropriate estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been conducted on the relationships of character strengths with different indicators of well-being. Overall, findings suggest that almost all character strengths positively relate to subjective and psychological well-being (Hausler et al, 2017;Wagner et al, 2020), physical well-being (Proyer et al, 2013), general health (Gander et al, 2020), as well as life satisfaction (Buschor et al, 2013), and job satisfaction (Jungo et al, 2008;Heintz and Ruch, 2020). The exceptions are the strengths of modesty, prudence, appreciation of beauty and excellence, and judgment, for which often small negative relationships (modesty), no relationships, or small positive relationships with well-being (prudence, beauty, and judgment) are reported.…”
Section: Character Strengths and Job And Life Satisfactionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite character strengths being seen as stable traits, they are also considered malleable due to cultivation or deliberate interventions. Accordingly, Gander et al (2018) explored the stability and malleability of character strengths and their relations to well-being applying a longitudinal study with more than 1700 participants. Their results provide an important basis for intervention studies addressing the promotion of character strengths and well-being of individuals.…”
mentioning
confidence: 99%